DESAIN ENERGI HIBRIDA SOLAR PANEL DAN LISTRIK UNTUK PENERANGAN AREA PARKIR - Widodo, Sarono; Rochadi, Agus; Anif, Muhammad (Jurnal Teknologi Terapan, 2019)
The design of hybrid energy by utilizing solar energy and electrical energy (PLN) is further research as a source of energy for cell model lighting in the parking area. The electricity generated from the sun through solar panels stored on the battery as the primary source through a hybrid system. The system is designed using two solar panels (110 Wp), Mesonic MF 1500 and Deep cycle 12V / 100Ah batteries to supply 100 - 250-watt parking lot lighting for three to four hours. With this hybrid method, the use of electrical energy for lighting can be supplied complete with solar panels.